Faktor-faktor yang Mempengaruhi Kecemasan Antenatal - Nety Mawarda Hatmanti; Rusdianingseh Rusdianingseh; Yurike Septianingrum; Siti Maimunah (The Indonesian Journal of Health Science, 2021)
Anxiety during pregnancy is something that can happen to every mother and is a natural thing. As a health worker, of course looking for the cause of anxiety will be very important to determine the next action or step to overcome the anxiety that occurs. The purpose of this study was to analyze self-efficacy, parity and age at marriage on the anxiety of pregnant women.This study uses a cross-sectional technique, the independent variables are self-efficacy, parity and age at marriage. The dependent variable is anxiety in pregnant women. Total population of 139 pregnant women, with simple random sampling technique obtained a sample of 103 pregnant women.The results of the study were that most of the pregnant women (82.5%) were in the age range 20 years, most (61.2%) had a secondary education level and most (70.9%) did not work. Using the Pearson Correlation test (product moment correlation) and multiple linear regression, it was found that parity (0.007) and self-efficacy (0.041) were weakly related to anxiety in pregnant women and parity variable (-0.214) was the most influential on anxiety during pregnancy. .There is a need for comprehensive education and counseling for couples of childbearing age to manage the distance between pregnancies and the number of children, to reduce maternal anxiety during pregnancy.